Controlling the Dji Ryze Tello Drone Using Human Hand Gestures - Widodo; Andoy, Aldis S; Tayane, Rosalin T; Supriadi, Iyus (International Journal of Applied Research and Sustainable Sciences, 2024)
Computer vision is an important part of the development of modern technology. One of the highlights is the introduction of hand movement, which integrates artificial intelligence into device controls. In the use of devices, especially drones or robots, this technology allows control without the need for additional devices such as remote control. Objectives Research applied technology Gesture Identification Hand drone DJI Ryze Tello. This application involves using Python 3 as a programming language, PyCharm as an editor, the OpenCV Library and Google MediaPipe (Hands) for real-time image processing and hand tracking. Research results show that drone control through hand gestures in front of a webcam can be done successfully, highlighting the potential of CVs to improve user interfaces on modern devices